Assessment of asthma severity according to treatment steps in Japanese pediatric patients: a descriptive cross-sectional study using an administrative claims database. (2nd December 2021) - Yoshida, Satomi; Tanaka, Shiro; Adachi, Yuichi; Yoshisue, Hajime; Kozawa, Masanari; Kawakami, Koji
Abstract: Objectives: Japan has one of the highest asthma prevalence rates in Asia; however, there is a lack of epidemiological studies on asthma among children in Japan. This study aimed to describe the severity of asthma and the prescription patterns for its treatment among pediatric patients, by using a large-scale claims database. Methods: The analysis datasets were extracted from the JMDC database for the period of April 1, 2009 to March 30, 2015; included records were restricted to patients between 2 and 15 years of age. The Japanese Pediatric Guidelines for the treatment and management of asthma (JPGL) steps were used as a proxy for asthma treatment and severity. We also described the characteristics of asthma in children by stratifying the prevalence and incidence cohorts by index years. Results: In the prevalence cohort (56% male), from 2010 to 2014, approximately 80–90% of the children received step 1 or 2 treatment, with the remainder receiving step 3 or 4 treatment, as defined by the JPGL. The majority (approximately 90%) of patients visited clinics for asthma treatment, while a minority visited hospitals. Conclusions: Our study showed the severity of asthma among Japanese pediatric patients, as well as their demographic characteristics, using a large-scale claims database. The majority of pediatric asthma patients received treatment for mild-to-moderate asthma, while less than 10% received treatment for severe asthma.